UTILIZING PICTURE STORIES TO ENHANCE READING COMPREHENSION NARRATIVE TEXT TO SECOND GRADE STUDENTS - Hasmila; Erwin Akib; Junaid (English Language Teaching Methodology, 2021)
The objective of the analysis was to distinguished whether or not or not the utilization of image stories to boost reading comprehension on narrative text of second grade students of SMPN three Lembang in year 2020/2021. The tactic during this analysis used similar experimental analysis. The quasi-experimental analysis designed were used 2 categories that were schooled 2 completely different methodology. The experiment cluster was schooled with image stories, and also the management cluster was schooled standard. The population at the second grades students of SMPN three Lembang carries with it seventy five students, the sample were of forty eight students (26 students) experimental cluster and twenty two students (controlled class). Bearing on the applied mathematics result, the findings of this analysis showed that the mean score of post-tests for the experimental cluster was seventy nine.23, whereas the mean score of post-tests for the management cluster was seventy six.40. it implies that the mean score of the experimental cluster was bigger than will the management teams. it absolutely was obtained that t-test was four.36 and also the t-table was a pair of.51 for alpha (α) zero.05. The t-test was beyond t-table (86.08 > 4.042) It implies that H1 was accepted and metallic element was rejected. supported the findings of this analysis, it is terminated that the used of image stories as methodology to boost reading comprehension on narrative text of second grade students at SMPN three Lembang in pedagogy was effective to enhance the students’ reading skills